Induction of Krüppel-Like Factor 4 Mediates Polymorphonuclear Neutrophil Activation in Streptococcus pneumoniae Infection - Bhattacharyya, Aritra; Herta, Toni; Conrad, Claudia; Frey, Doris; García, Pedro; Suttorp, Norbert; Hippenstiel, Stefan; Zahlten, Janine (Frontiers in Microbiology, 2021)
The recruitment and activation of polymorphonuclear neutrophils (PMNs) is of central importance for the The recruitment and activation of polymorphonuclear neutrophils (PMNs) is of central importance for the elimination of pathogens in bacterial infections. We investigated the S. pneumoniae-dependent induction of the transcription factor Krueppel-like factor (KLF) 4 in PMNs as a potential regulator of PMN activation. We found that KLF4 expression is induced in human blood-derived PMNs in a time- and dose-dependent manner by wild-type S. pneumoniae and capsule knockout mutants. Unencapsulated knockout mutants induced stronger KLF4 expression than encapsulated wild-types. The presence of autolysin LytA-competent (thus viable) pneumococci and LytA-mediated bacterial autolysis were required for KLF4 induction in human and murine PMNs. LyzMcre-mediated knockdown of KLF4 in murine blood-derived PMNs revealed that KLF4 influences pneumococci killing and increases the release of the proinflammatory cytokines tumor necrosis factor alpha (TNFα) and keratinocyte chemoattractant (KC) and decreases the release of the anti-inflammatory cytokine IL-10. Thus, S. pneumoniae induces KLF4 expression in PMNs, which contributes to PMN activation in S. pneumoniae infection.